High and ultra‐high definition of infrared spectral histopathology gives an insight into chemical environment of lung metastases in breast cancer. Issue 4 (6th January 2019) - Augustyniak, Karolina; Chrabaszcz, Karolina; Jasztal, Agnieszka; Smeda, Marta; Quintas, Guillermo; Kuligowski, Julia; Marzec, Katarzyna M.; Malek, Kamilla
Abstract : Using high definition (HD) and ultra‐high definition (UHD) of Fourier‐transform infrared (FTIR) spectroscopic imaging, we characterized spectrally pulmonary metastases in a murine model of breast cancer comparing them with histopathological results (Hematoxylin and eosin [H&E] staining). This comparison showed excellent agreement between the methods in case of localization of metastases with size below 1 mm and revealed that label‐free HD and UHD IR spectral histopathology distinguish the type of neoplastic cells. We primary focused on differentiation between metastatic foci in the pleural cavity from cancer cells present in lung parenchyma and inflamed cells present in extracellular matrix of lungs due to growing of advanced metastases. In addition, a combination of unsupervised clustering and IR imaging indicated the high sensitivity of FTIR spectroscopy to identify chemical features of small macrometastases located under the pleural cavity and during epithelial‐mesenchymal transition. FTIR‐based spectral histopathology was proved to detect not only phases of breast cancer metastasis to lungs but also to differentiate various origins of metastases seeded from breast cancer. Abstract : Fourier‐transform infrared (FTIR)–based spectral histopathology is proven as a reliable tool for the characterization of the progressive metastasis from breast cancer to lungs. This technique in combination with unsupervised clustering localizes metastases with a size below 1 mm. FTIR spectral features differentiate metastatic foci under the pleural cavity from metastases present in the parenchyma and during epithelial‐mesenchymal transition. Inflammatory cells in the extracellular matrix are also detected.